双鼓修形直齿圆柱齿轮加载接触分析 - 李智超; 邓效忠; 蒋闯; 石佩斐 (Jixie Chuandong, 2014)
A new method of cylindrical gear modification,namely double drum gear modification is studied. Bending deformation of cylindrical gear under the action of the load is deduced,the tooth surface equation of the double drum repairing is established,the modification coefficient based on bending deformation is identified. And the coordinates of points on the surface of the tooth before and after the modification is designed and operated by the process on Matlab. The assembly model before and after modification is established after import the coordinates to UG. The contact area of the gear is simulated by using the method of involvement and the stress analysis is carried out by ANSYS,then the equivalent stress distribution of loaded gear is obtained.The meshing performance analysis shows that the pair of gear has the better mesh performance after the modification and the correctness of modification theory is verifed.